KEGAGALAN PROSES MANUFAKTUR DALAM PEMBUATAN GATE LEAF PINTU AIR SERTA UPAYA PENANGGULANGAN - Sunarto Sunarto (Wahana Teknik, 2012)
Deformation occurred during fabrication of Gate Leaf for dam construction was found to cause severe problems. The problems involved can be categorized as difficulty in assembling and erection of the component in the site plant. As a result construction strength would be lowered despite unfitted geometrical shape and in efficiency in production cost. In this thesis, the deformation described above was investigated based on the literature studies. The discussion was focused on characterization and elimination of technical problems that arisen from manufacturing operation. Therefore repairs would be reduced to a lower level besides quality improved. Research data was collected from direct observation in the field and report from previous production failures. A careful theoretical assessment came to the conclusion that deformation was particularly due to welding process which specifically could be identified as improper welding procedure, over deposited weld pool, unsuitable design and position of welding jigs. The studies also suggested that the manufacturing of the Gate Leaf component need to be supported with a correct implementation of production management, manufacturing operation procedure, as well as continuous quality inspection. The investigation indicated that human resource quality need to be improved in their technical skill, (ie: welding technology and construction design). This knowledge should have orientation in manufacturing skill and thereby improvement of welding engineer and welding inspector is essential in order to reduce risk of deformation. Keywords : Gate Leaf, Deformation, Manufacture